Stages of development of artificial intelligence in the banking sector - V. L. Parkhomenko; I. S. Kulaeva (Путеводитель предпринимателя, 2024)
Artificial intelligence is transforming many areas of activity, including completely transforming banks. Artificial intelligence offers solutions to improve the rationality of decisions, the speed and accuracy of information processing, the provision of ready–made solutions and the implementation of monitoring operations. This article examines the evolution of artificial intelligence in the banking sector. The key areas of AI use in the financial market are highlighted, such as scoring and underwriting, anti–fraud, investment portfolio management, robo–consulting, monitoring client requests and others.The subject of the research in the article is the system of relations arising during the transformation of the banking sector with the introduction of artificial intelligence.